Deciduosis of the appendix: a case report (Research, Society and Development, 2022)
Introduction: Ectopic deciduosis refers to decidual tissue outside the uterus. Ectopic decidua appears on the surface of the female reproductive organs and peritoneum; however, rare cases can be found in the appendix, lymph nodes, lungs, kidneys, and skin. Deciduosis is a benign condition that usually does not cause any symptoms and resolves spontaneously 4-6 weeks after delivery. However, an ectopic decidua involving the appendix wall often causes appendicitis and presents with acute abdominal signs. Methodology: The descriptive study of the case report type and the data obtained from the patient's medical record. Case presentation: This paper reports a woman aged 29 years with complaints of abdominal pain, like being stabbed in the pit of the stomach and then to the lower right abdomen for two days. A physical examination revealed tenderness in the lower abdomen with a positive McBurney sign. At that time, the patient was pregnant with a gestational age of 20-21 weeks. The patient underwent an appendectomy with the tissue sent to the anatomic pathology laboratory with the presence of decidual cells in the subserous layer and serous fat, and it was concluded as deciduosis of the appendix. Conclusion: Based on clinical and laboratory findings, the patient was diagnosed with deciduosis of the appendix.